Epistemologija vrlin in Nezemljani - Šuster, Danilo (Anthropos (Ljubljana), 2024)
Open-mindedness is a central epistemic virtue. Sometimes it is inferred as a conclusion in the scheme: ‘No one has disproved that p. It is possible that p is true. Therefore, we should keep an open mind as regards p.’ The conclusion is unjustified when we commence with ignorance (an intellectual failing), infer weak epistemic possibility (bare compatibility with the knowledge base) and conclude with mere openness. However, radical skeptical arguments are not fallacious, but they are not cogent either, one of the premises can be rationally refuted. Moreover, even a weaker type of possibility, if serious, can justify inquiry. The seriousness of an epistemic possibility sometimes depends on pragmatic factors of the epistemic situation (pragmatic encroachment). I accept the distinction between suspension (active, goal oriented, connected with inquiry) and agnosticism (merely being neutral). Some questions remain inherently unanswerable, serving as a testament to our deep ignorance—a stark contrast to the rationality of open-mindedness. Epistemic dilemmas are illustrated with the con troversies surrounding UAP (unrecognized anomalous phenomena).
Keywords: epistemska možnost; epistemske vrline; nevednost; skepticizem; širokomiselnost; vzdržanje sodbe